2008
DOI: 10.1002/app.28001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cupric ion on thermal degradation of chitosan

Abstract: The thermal degradation of chitosan and chitosan-cupric ion compounds in nitrogen was studied by thermogravimetry analysis and differential thermal analysis (DTA) in the temperature range 30-6008C. The effect of cupric ion on the thermal degradation behaviors of chitosan was discussed. Fourier transform-infrared (FTIR) and X-ray diffractogram (XRD) analysis were utilized to determine the micro-structure of chitosan-cupric ion compounds. The results show that FTIR absorbance bands of À ÀNÀ ÀH, À ÀCÀ ÀNÀ À, À ÀC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…2b). Theses peaks could be due to the chain deacetylation and to decompositions involving the main chain (Ou et al, 2008). A thermal decomposition step followed by volatilization of by products could be detected both as endothermic or exothermic peaks, depending on the balance between both processes.…”
Section: Thermal Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…2b). Theses peaks could be due to the chain deacetylation and to decompositions involving the main chain (Ou et al, 2008). A thermal decomposition step followed by volatilization of by products could be detected both as endothermic or exothermic peaks, depending on the balance between both processes.…”
Section: Thermal Analysesmentioning
confidence: 97%
“…This could be due to the decomposition of acetylated units, already correlated to an endothermic process (Nieto & Peniche-Covas, 1991). In the literature various remarks were made on the thermal decomposition of chitosan, since only exothermic (Ou et al, 2008) or only endothermic (Chuang, Young, Yao, & Chiu, 1999) peaks were mentioned. The thermal properties of chitosan are dependant on degree of acetylation, crystallinity, average molecular weight and probably are at the origin of the different data found in the literature.…”
Section: Thermal Analysesmentioning
confidence: 98%
“…The DSC curve for the chitosan film obtained after dissolution in NaOH/thiourea (Almeida et al 2010) showed two peaks, an endothermic peak at 225°C and an exothermic peak near 275°C. These peaks are probably related to the deacetylation of the chain and to decompositions involving the main chain (Ou et al 2008).…”
Section: Thermal Analyses Tg and Dsc Resultsmentioning
confidence: 96%
“…10-12 show thermal gravimetric analysis (TGA) of chitosan and chitosanmetal complexes (Ch-Fe, Ch-Co, and Ch-Ni) [16] in three different ratios indicated that chitosan and chitosan-metal complexes proceed in two stages: the first stage explained the water weight loss, while the second one is the degradation of chains with greater weight loss, Table (2) shows the weight loss percentages of two stages for chitosan and chitosan-metal complexes. …”
Section: Tga Analysismentioning
confidence: 99%
“…Determination of activation energy of decomposition of chitosan and chitosanmetal complexes [16] The activation energy was determined by the Arrhenius relationship according to Broido method in Eq.1. (1) where Ea is the activation energy (J mol Electrical conductivity measurements of chitosan and chitosan-metals ions complexes [19,20] The electrical conductivity (σ) was calculated from Eq.3…”
Section: Morphological Thermal and Electrical Studiesmentioning
confidence: 99%